Usos estratégicos da recuperação judicial - Maria Luísa Estanislau Reis (2018)
This dissertation, located in the field of Economic Analysis of Law, has as general theme the Judicial Recovery and as a specific theme the use of the legal norms of the institute by the debtor, the State Judge and the creditors whose credits were covered by the proposal of payment, directed by the following problem: the Judicial Recovery process is effective, that is, can the Bankruptcy and Corporate Recovery Act be able to condition the conduct of the parties and the magistrate in order to promote the protected interests, guiding principles and the objectives sheltered by the legislation? Faced with this questioning and in accordance with the theoretical framework of the Game Theory, the hypothesis was formulated that the normative body is not able to prevent subjects from making strategic uses of their special rules of substantive law and procedural law, causing, as a consequence, ineffective results for the process. To refute or confirm it, initially, in the First Chapter, the interpretative research method was applied, the protected interests, the guiding principles and the objectives protected by the institute were studied. Subsequently, in the Second Chapter, the interpretive research method was also applied and the incentive structure of Law n. 11.101 / 2005. In a third moment, in the Third Chapter, the diagnostic research method was initially applied and the institute was described by means of a logical-formal game model, representing it theoretically and abstractly. Then, the interpretive research method was applied and the results and solutions of the model were analyzed, finally to compare them with the protected interests, the guiding principles and objectives sheltered by institute and, therefore, evaluating their effectiveness. In addition to this theoretical research, an empirical investigation of the Judicial Recovery processes judged in the Business Courts of the Comarca of Belo Horizonte (MG) between 05/29/2008 and 12/29/2016 was conducted, which the results were presented and analyzed in Chapter Four. At the end, the Conclusion was outlined, confirming the hypothesis formulated in response to the problem question and providing perspectives for future research.